DESAIN SISTEM PENGENDALIAN MANAJEMEN SEBAGAI FAKTOR PENENTU KEBERHASILAN IMPLEMENTASI STRATEGI PERUSAHAAN - Ade Riadi; Aceng Abdul Hamid (PT. Hasba Edukasi Mandiri, 2026)
This study examines the role of management control system (MCS) design as a determinant of successful strategy implementation in firms. Strategy execution failures are commonly attributed to weaknesses in strategy formulation, yet contemporary literature indicates that the primary cause lies in poorly designed control systems that fail to translate strategy into measurable, monitored, and adaptable operational actions. Using a narrative literature review method that synthesizes classical control theories with contemporary empirical studies published between 2020 and 2025, this article examines how management control system design functions as a determinant of strategy implementation success. The review identifies four interrelated dimensions of MCS design that determine implementation success: strategic alignment, performance-risk integration, the balance between formal and informal controls, and the system's adaptive capacity to environmental change. Imbalance in any of these dimensions can create misalignment that gradually leads to implementation failure, even when the underlying strategy is conceptually sound. This article proposes a conceptual model of MCS design as a determinant of strategy implementation success that can serve as a basis for further empirical testing as well as a diagnostic framework for practitioners.